Jeremy Dibble, Michele Esposito (2010) - Klein, Axel (Journal of the Society for Musicology in Ireland, 2010)
A review, by Axel Klein, of Jeremy Dibble, Michele Esposito (Dublin: Field Day Publications, 2010), ISBN 978-0-946755-47-9.